Debugging Assessment Workshop: A Game-Based Debugging Assessment for Accessible and Scalable K-12 Evaluation (Constructionism Conference Proceedings, 2025)
Debugging is a critical component of computational thinking and an essential skill for problem-solving. Over the past decade, national school curricula have started to include debugging practices, underscoring its importance, but to date there is no standardized assessment method available. Similarly, research on debugging assessment is scarce and the solutions brought forth lack scalability and accessibility to be applied in K-12 education. This workshop addresses this gap by introducing a novel game-based debugging assessment tool that enables students across a wide range of ages and skill levels to engage in realistic debugging tasks without requiring any prior programming knowledge. The tool focuses on the actual debugging aspect of problem-solving and programming by guiding students to check for bugs, locate them, and experiment with different solutions to effectively resolve the issue and achieve the desired outcome. The assessment strives to provide realistic debugging features with multiple valid solutions, interdependent variables, and time constraints, while distinguishing between superficial fixes and root-cause resolutions to mimic real-world debugging challenges. Implemented as a cross-platform tablet application, the assessment was developed iteratively with learners aged 5 to 18+, to ensure appropriate engagement across the K-12 age range. In this workshop, participants will be able to try this novel debugging assessment tool first-hand, share feedback on its debugging principles, discuss strategies for integrating such assessments into classrooms, and explore opportunities for collaboration.